2019
DOI: 10.30659/odj.6.2.113-117
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity Antibacterial Zinc Oxide Eugenol With Zinc Oxide Propolis for Endodontic Treatment in Primary Teeth

Abstract: Background: Enterococcus faecalis is generally found on the failure of root canal treatments. Zinc oxide propolis is believed to have an antibacterial effect on that bacteria. This research aimed to compare bacteriostatic effect of zinc oxide eugenol (ZOE) and zinc oxide propolis (ZOP) as the sealer materials of root canal.Method: This was an experimental research with post-test only control group design with two different groups (ZOE and ZOP). Culture of Enterococcus faecalis bacteria was smeared on Blood Aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…12 Bacterial growth can be inhibited by flavonoids because it can form complexes with proteins through hydrogen bonding. 16 The function of flavonoid in inhibiting the growth of Enterococcus faecalis has a mechanism by inhibiting the function of the bacterial cytoplasmic membrane by forming complex compounds with extracellular proteins so it can damage the cytoplasmic membrane of bacterial cells followed by the release of intracellular compounds, loss of cations and macromolecules from cells, cause disruption of cell growth and bacterial cell death, this causes the growth of Enterococcus faecalis bacteria were inhibited. 17,18 The next metabolite compound of kelakai leaf that act against the Enterococcus faecalis bacteria is saponin.…”
Section: Resultsmentioning
confidence: 99%
“…12 Bacterial growth can be inhibited by flavonoids because it can form complexes with proteins through hydrogen bonding. 16 The function of flavonoid in inhibiting the growth of Enterococcus faecalis has a mechanism by inhibiting the function of the bacterial cytoplasmic membrane by forming complex compounds with extracellular proteins so it can damage the cytoplasmic membrane of bacterial cells followed by the release of intracellular compounds, loss of cations and macromolecules from cells, cause disruption of cell growth and bacterial cell death, this causes the growth of Enterococcus faecalis bacteria were inhibited. 17,18 The next metabolite compound of kelakai leaf that act against the Enterococcus faecalis bacteria is saponin.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 ] reported the new ZOP paste (zincoxide with propolis ) achieved clinical success rate of 93.8% and radiographic success rate of 62.5% after 12 months, while ZOE achieved clinical success rate 87.5% and radiographic success rate 56.3% after 12 months. Another study by Rahman and Christiono[ 33 ] concluded that ZOP has lower antibacterial effectiveness on the Enterococcus faecalis than ZOE. Gupta et al .…”
Section: Discussionmentioning
confidence: 99%
“…107 Since 1930s, ZnO has been most widely used as a root canal lling material. 108 It has been reported that nanosize materials play a signicant role in the regenerative endodontic eld and disinfection of the root canal space. It is known that ZnO is nearly insoluble in water due to high polarity; therefore, nanostructures of ZnO might be helpful to overcome this limitation.…”
Section: Endodonticmentioning
confidence: 99%